2020
DOI: 10.3390/geosciences10110425
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review on Data-Driven Models for Predictive Maintenance of Railway Track: Implications in Geotechnical Engineering

Abstract: Conventional planning of maintenance and renewal work for railway track is based on heuristics and simple scheduling. The railway industry is now collecting a large amount of data with the fast-paced development of sensor technologies. These data sets carry information about the conditions of various components in railway track. Since just before the beginning of the 21st century, data-driven models have been used in the predictive maintenance of railway track. This study presents a systematic literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 109 publications
(107 reference statements)
0
15
0
Order By: Relevance
“…It is worth mentioning that beside ANN, there exist other techniques such as convolutional neural network (CNN), recurrent neural networks (RNN) and long short-term memory (LSTM) which can be used for the purpose of prediction. CNNs are particularly designed for image data [21,22] and RNN and LSTM are widely used to analyse time series and sequence data [21,23,24]. In this study, we choose ANN due to its ability to easily explore the importance of the input features on the output parameter.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that beside ANN, there exist other techniques such as convolutional neural network (CNN), recurrent neural networks (RNN) and long short-term memory (LSTM) which can be used for the purpose of prediction. CNNs are particularly designed for image data [21,22] and RNN and LSTM are widely used to analyse time series and sequence data [21,23,24]. In this study, we choose ANN due to its ability to easily explore the importance of the input features on the output parameter.…”
Section: Introductionmentioning
confidence: 99%
“…For the unsupervised AD task, unsupervised methods are used for comparison. First, we compare our results to a statistical measure called the dynamic coefficient (dynCoeff ) -see (2). This coefficient describes the ratio of the maximum dynamic to the static wheel load within each sensor measurement x.…”
Section: Alternative Methods For Comparisonmentioning
confidence: 99%
“…Hence, railway operators need to ensure safe and reliable operations while being economically efficient. With an increasing investment in condition monitoring (CM) devices, the implementation of data-driven solutions for fault detection and diagnostics has become a promising direction [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Although ML/DL methods developed for the PdM practices in a wide range of applications, the literature with specific applications in the railway industry is yet scarce. A recent review regarding the data-driven PdM works in the railway tracks can be found in [ 96 ]. The works have been classified based on model types and application types.…”
Section: Data-driven Pdm For the Railway Industrymentioning
confidence: 99%